(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article highlights the causes of dermatophytosis in farm animals, their economic and sanitary-hygienic significance, as well as methods of diagnosis and prevention. The study examined the seasonal distribution and epidemiological features of trichophytosis in pedigree cattle and explored effective measures for its control. The obtained results are of great scientific and practical importance for reducing the spread of dermatophytosis and maintaining a healthy gene pool in livestock farming.